Stochastic risk analysis and management - Harlamov, Boris, author (Mathematics and statistics series (ISTE), 2017)
Mathematical Bases -- Cramér-Lundberg Model -- Models With the Premium Dependent on the Capital -- Heavy Tails -- Some Problems of Control.